2020
DOI: 10.3390/nano10061115
|View full text |Cite
|
Sign up to set email alerts
|

Relaxometric Studies of Gd-Chelate Conjugated on the Surface of Differently Shaped Gold Nanoparticles

Abstract: Nowadays, magnetic resonance imaging (MRI) is one of the key, noninvasive modalities to detect and stage cancer which benefits from contrast agents (CA) to differentiate healthy from tumor tissue. An innovative class of MRI CAs is represented by Gd-loaded gold nanoparticles. The size, shape and chemical functionalization of Gd-loaded gold nanoparticles appear to affect the observed relaxation enhancement of water protons in their suspensions. The herein reported results shed more light on the determinants of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…As a result, 13 times higher relaxivity than that of the currently used clinical contrast agents was observed. Of the two NPs, PEG-Gd@CCNPs had the highest relaxivity, making them a promising candidate for MRI contrast agent [94]. PEG is a widely used polymer that offers stability and biocompatibility to gold nanoparticles.…”
Section: Consolidation Of Gold and Gadolinium Nanoparticles 41 Applic...mentioning
confidence: 99%
“…As a result, 13 times higher relaxivity than that of the currently used clinical contrast agents was observed. Of the two NPs, PEG-Gd@CCNPs had the highest relaxivity, making them a promising candidate for MRI contrast agent [94]. PEG is a widely used polymer that offers stability and biocompatibility to gold nanoparticles.…”
Section: Consolidation Of Gold and Gadolinium Nanoparticles 41 Applic...mentioning
confidence: 99%
“…The research proved that concave cube AuNPs are capable of producing brighter contrast compared with spherical ones. [132]…”
Section: Size and Shapementioning
confidence: 99%
“…Research has shown that CAs with Gd as the magnetic center exhibit excellent T 1 /T 2 dual-mode imaging possibilities [ 4 ]. Recently, most dual-mode T 1 and T 2 MRI CAs have been designed as NPs with Gd shells [ 5 , 6 , 7 , 8 ]; in this study we propose a special 2D-structured Gd compound with remarkable T 1 and T 2 imaging functions.…”
Section: Introductionmentioning
confidence: 99%